Increased contrast enhancement of the parent vessel of unruptured intracranial aneurysms in 7T MR imaging. (18th May 2020) - Samaniego, Edgar A; Roa, Jorge A; Zhang, Honghai; Koscik, Timothy R; Ortega-Gutierrez, Santiago; Bathla, Girish; Sonka, Milan; Derdeyn, Colin; Magnotta, Vincent A; Hasan, David
Abstract : Background: Inflammation of the arterial wall may lead to aneurysm formation. The presence of aneurysm enhancement on high-resolution vessel wall imaging (HR-VWI) is a marker of wall inflammation and instability. We aim to determine if there is any association between increased contrast enhancement in the aneurysmal wall and its parent artery. Methods: Patients with unruptured intracranial aneurysms (UIAs) prospectively underwent 7T HR-VWI. Regions of interest were selected manually and with a semi-automated protocol based on gradient algorithms of intensity patterns. Mean signal intensities in pre- and post-contrast T1-weighted sequences were adjusted to the enhancement of the pituitary stalk and then subtracted to objectively determine: circumferential aneurysmal wall enhancement (CAWE); parent vessel enhancement (PVE); and reference vessel enhancement (RVE). PVE was assessed over regions located 3- and 5 mm from the aneurysm's neck. RVE was assessed in arteries located in a different vascular territory. Results: Twenty-five UIAs were analyzed. There was a significant moderate correlation between CAWE and 5 mm PVE (Pearson R=0.52, P=0.008), whereas no correlation was found between CAWE and RVE (Pearson R=0.20, P=0.33). A stronger correlation was found between CAWE and 3 mm PVE (Pearson R=0.78, P<0.001). Intra-class correlation analysis demonstrated good reliability between measurements obtained using semi-automated and manual segmentation (ICC coefficient=0.790, 95% CI 0.58 to 0.90). Conclusion: Parent arteries exhibit higher contrast enhancement in regions closer to the aneurysm's neck, especially in aneurysms≥7 mm. A localized inflammatory/vasculopathic process in the wall of the parent artery may lead to aneurysm formation and growth.